Canadian Macroeconomics: Problems and Policies - Lyons, Brian (Ontario Prentice Hall Canada Inc., 1983)
Canadian Macroeconomics: Problems and Policies. This book is an introductory macroeconomics text that addresses itself to the major economic problems facing Canada and Canadians today, and the policy choices confronting goverments in dealing with these issues. It is not oriented toward rigorous, abstract or elegant economics theory, nor to a mathematical approach to economics students of introductory economics neither want nor need these.
Keywords: Economics